Organizational factors associated with health worker protection during the COVID-19 pandemic in four provinces of South Africa - Muzimkhulu Zungu; Kuku Voyi; Nosimilo Mlangeni; Saiendhra Vasudevan Moodley; Jonathan Ramodike; Nico Claassen; Elizabeth Wilcox; Nkululeko Thunzi; Annalee Yassi; Jerry Spiegel; Molebogeng Malotle (BMC, 2021)
Abstract Background Health workers, in short supply in many low-and-middle-income countries, are at increased risk of SARS-CoV-2 infection. This study aimed to assess how South Africa, prepared to protect its health workers from SARS-CoV-2 infection. Methods This was a cross-sectional study design applying participatory action research in four provinces of South Africa. A semi-structured questionnaire and a qualitative observational HealthWISE walkthrough risk assessment was carried out to collect data on occupational safety and health (OSH) systems in 45 hospitals across four provinces to identify factors associated with health worker protection. Adapting the International Labour Organization (ILO) and World Health Organization (WHO) HealthWISE tool, we compiled compliance scores through walkthrough surveys. We used logistic regression to analyze the relationship between readiness indicators and the actual implementation of protective measures. Results We found that health facilities in all four provinces had SARS-CoV-2 plans for the general population but no comprehensive OHS plan for health workers. Provincial Departments of Health (PDoH) varied in how they were organized to respond: Provinces A and D had an OSH SARS-CoV-2 provincial coordinating team and a dedicated budget for occupational health; Province A had an occupational health doctor and nurse; while Province B had an occupational health nurse; Province A and D PDoHs had functional OSH committees; and Province D had conducted some health risk assessments specific to SARS-CoV-2. However, none of the assessed health facilities had an acceptable HealthWISE compliance score (≥ 75%) due to poor ventilation and inadequate administrative control measures. While the supply of personal protective equipment was adequate, it was often not worn properly. Our study found that having an OSH SARS-CoV-2 policy was significantly associated with higher personal protective equipment and ventilation scores. In addition, our analysis showed that hospitals with higher compliance scores had significantly lower infection rates (IRR 0.98; 95% CI: 0.97, 0.98). Conclusions Despite some initial preparedness, greater effort to protect health workers is still warranted. Low-and-middle-income countries may need to pay more attention to OSH systems and consider using tools, such as ILO/WHO HealthWISE tool, to protect health workers' health.